1980
DOI: 10.1039/c39800000789
|View full text |Cite
|
Sign up to set email alerts
|

Thermal evaporation of intact positive ions of quaternary ammonium and phosphonium salts

Abstract: Evidence is presented for a purely thermal evaporation of intact positive ions of quaternary ammonium and phosphonium salts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The hypothesis that ions can be formed in a field‐independent thermal desorption process was initially proposed by Holland et al17 in connection with a model for ionization by field desorption (FD) and it was later unambiguously observed in the thermal evaporation of quaternary ammonium and phosphonium salts in vacuo by Stoll and Röllgen18 as well as by Cotter and Yergev 19. The present work, however, appears to represent the first case of thermal desorption of organic salts at atmospheric pressure.…”
mentioning
confidence: 58%
“…The hypothesis that ions can be formed in a field‐independent thermal desorption process was initially proposed by Holland et al17 in connection with a model for ionization by field desorption (FD) and it was later unambiguously observed in the thermal evaporation of quaternary ammonium and phosphonium salts in vacuo by Stoll and Röllgen18 as well as by Cotter and Yergev 19. The present work, however, appears to represent the first case of thermal desorption of organic salts at atmospheric pressure.…”
mentioning
confidence: 58%
“…This has been shown conclusively to be a thermal evaporation of ions under vacuum for quaternary ammonium and phosphonium salts. 10 Chen et al 11 recently showed that some organic salts could be thermally desorbed as ions into the gas phase under ambient conditions, a process they termed atmospheric pressure thermal desorption ionization (APTDI).…”
Section: Thermal Desorption/ionizationmentioning
confidence: 99%
“…The hypothesis that ions can be formed in a fieldindependent thermal desorption process was initially proposed by Holland et al [17] in connection with a model for ionization by field desorption (FD) and it was later unambiguously observed in the thermal evaporation of quaternary ammonium and phosphonium salts in vacuo by Stoll and Röllgen [18] as well as by Cotter and Yergev. [19] The present work, however, appears to represent the first case of thermal desorption of organic salts at atmospheric pressure.…”
mentioning
confidence: 98%